Russian-Belarusian hybrid activities on the borders of the European Union and NATO - Andrzej Wawrzusiszyn (Journal of Modern Science)
Objectives The complexity of the threats at the eastern border of the European Union (EU) and NATO is primarily related to the war taking place in Ukraine. Both Poland and the other Baltic States are subjected to controlled migration pressure at the border with Belarus and Russia. The intensification of these actions observed since 2021 has become part of a process of instrumentalisation of migration and an attempt to trigger population movements towards Europe. The procedure is accompanied by a wide range of military and non-military actions, overt and covert measures, including disinformation, cyber-attacks, economic pressure, the use of irregular armed groups and regular troops. The purpose of this discussion is to characterise what is referred to as hybrid activities and their impact on the organisation and security management of the eastern EU and NATO border, as well as the societies of the bordering states.